# Deriving a Taylor series from a rational quadratic and determining its interval of convergence

Write $f(x)=\frac{1}{x^2-4x+3}$ as a Taylor series centered at $a=2$ and determine the interval of convergence.

I'm having problems with constructing the Taylor series. So far, I've gotten

$$f(2)=-1$$ $$f'(2)=0$$ $$f''(2)=-2$$ $$f'''(2)=0$$ $$f''''(2)=-7584$$

but I can't seem to find the pattern. Am I missing something here?

• By the way, $f''''(2)=-24$. – Claude Leibovici Mar 15 '17 at 10:08

It is known (being a geometric series) that $$\frac{1}{1-u}=1+u+u^2+u^3+\dots\qquad |u|<1$$ and so by replacing $u$ by $u^2$ we get $$\frac{1}{1-u^2}=1+u^2+u^4+u^6+\dots\qquad |u|<1$$
We have\begin{align} \frac{1}{x^2-4x+3}&=\frac{1}{(3-x)(1-x)}\\ &=-\frac{1}{2}\bigg[\frac{1}{3-x}-\frac{1}{1-x}\bigg]\\ &=-\frac{1}{2}\bigg[\frac{1}{1-(x-2)}+\frac{1}{1+(x-2)}\bigg]\\ &=-\frac{1}{2}\cdot\frac{2}{[1-(x-2)^2]}\\ &=- \frac{1}{1-(x-2)^2}\qquad \text{write x-2=u to get}\\ &=-\frac{1}{1-u^2}\\ &=-\bigg[1+u^2+u^4+u^6 +\dots\bigg]\\ &=-1-u^2-u^4-u^6-\dots\\ &=-1-(x-2)^2-(x-2)^4-(x-2)^6-\dots \end{align} Since we must have $|x-2|<1$, we get $1<x<3$.
Start using $x=y+2$. This gives $x^2-4x+3=y^2-1$. So $$f(x)=\frac{1}{x^2-4x+3}=\frac{1}{y^2-1}=-\frac{1}{2 (1-y)}-\frac{1}{2 (1+y)}$$ Now, use well known expansions around $y=0$.